Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
 
\begin{equation} 1){y}'={(log_{9}x)}'=\frac{1}{x \ln 9}; \end{equation} \begin{equation} 2){y}'={(\frac{\ln x}{x^{3}})}'=\frac{\frac{1}{x}*x^{3}-\ln x*3x^{2}}{x^{6}}= \end{equation} \begin{equation} =\frac{x^{2}-3\ln x*x^{2}}{x^{6}}=\frac{x^{2}(1-3 \ln x)}{x^{6}}= \end{equation} \begin{equation} =\frac{1-3 \ln x}{x^{4}} \end{equation} \begin{equation} 3){y}'={(x^{5} \ln x)}'=5x^{4} \ln x+x^{5}*\frac{1}{x}= \end{equation} \begin{equation} =5x^{4} \ln x+x^{4}=x^{4}(5 \ln x+1). \end{equation}